The freedom to do God's will : religious fundamentalism and social change - Haar, Gerrie ter; Busuttil, James J. (Routledge, 2003)
A sensitive and topical overview of religious fundamentalism, examining traditions including Hinduism, Buddhism, Mormonism, Judaism, Christianity and Islam.